Screening and patient-tailored care for emotional and cognitive problems compared to care as usual in patients discharged home after ischemic stroke (ECO-stroke): a protocol for a multicenter, patient-blinded, cluster randomized controlled trial - J. P. L. Slenders; R. M. Van den Berg-Vos; C. M. van Heugten; J. M. A. Visser-Meily; S. M. A. A. Evers; R. J. de Haan; J. M. de Man-van Ginkel; V. I. H. Kwa (BMC, 2020)
Abstract Background Ischemic stroke patients with a good outcome in terms of motor functioning and communication are likely to be discharged home without further rehabilitation. A significant number of these patients experience cognitive and emotional problems resulting in lower quality of life and decreased participation in society. This paper presents the protocol of a study examining the clinical effectiveness, cost-effectiveness and implementation of an intervention focused on screening and patient-tailored care for cognitive and emotional problems as compared to usual care in patients discharged home after ischemic stroke. Methods / design A multicenter, patient-blinded, cluster randomized controlled trial will be performed. Centers will be randomized (1:1) to the intervention group or the usual care group. Patients (> 18 years old) with a neurological confirmed diagnosis of ischemic stroke who can be discharged home without follow-up treatment at an outpatient rehabilitation clinic will be included. In the intervention group, patients will receive a short, individualized, semi-structured consultation by specialized nurses in addition to usual care. This consultation includes 1) screening for cognitive and emotional problems, 2) screening for restrictions in participation, 3) promotion of self-management strategies and 4) a decision tool for referral to rehabilitation services. The intervention will be performed approximately 6 weeks after the stroke at the neurology outpatient clinics and will take approximately 60 min. The control group will receive care as usual. Both groups will be followed-up at 6 weeks, 3 months and 12 months after stroke. The primary outcome will be the level of participation measured with the Restriction subscale of the Utrecht Scale for Evaluation of Rehabilitation on the level of Participation (USER-Participation-R) at 12 months. A cost-effectiveness analysis and process evaluation will be performed alongside. Discussion This trial is the first to evaluate clinical effectiveness, cost-effectiveness and implementation of screening and patient-tailored care for cognitive and emotional problems compared to care as usual in patients discharged home after ischemic stroke. Potentially, this will improve the outcomes for patients with frequently occurring cognitive and emotional problems after stroke. Trial registration Netherlands Trial Register: NL7295 , registered 25 September 2018